1994
DOI: 10.1038/372546a0
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in skeletal muscle

Abstract: Reactive oxygen intermediates modulate skeletal muscle contraction, but little is known about the role of nitric oxide (NO). Here we show that rat skeletal muscle expresses neuronal-type NO synthase and that activity varies among several respiratory and limb muscles. Immunohistochemistry showed prominent staining of type II (fast) fibre cell membranes with antibodies against neuronal-type NO synthase. NO synthase activity in muscles correlated with type II fibre density. Resting diaphragm muscle produced detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
787
11
21

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 891 publications
(868 citation statements)
references
References 22 publications
49
787
11
21
Order By: Relevance
“…One is related to activation of guanylyl cyclase which decreases the force generation by skeletal muscle fibers [3]. The other involves a possible Snitrosylation of thiol groups in the sarcoplasmic reticulum such as those from the Ca 2+ pump [3]. In the present report, we investigate whether NO donors affect the Ca 2+ transport of sarcoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 89%
“…One is related to activation of guanylyl cyclase which decreases the force generation by skeletal muscle fibers [3]. The other involves a possible Snitrosylation of thiol groups in the sarcoplasmic reticulum such as those from the Ca 2+ pump [3]. In the present report, we investigate whether NO donors affect the Ca 2+ transport of sarcoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 89%
“…In skeletal muscle, nitric oxide mediates diverse functions related to fibre development, metabolism, contraction and blood flow (Lee et al, 1994;Kobzik et al, 1994;Roberts et al, 1997). Loss of nNOS may also result in aberrant regulation of adrenergic vasoconstriction (Thomas et al, 1998).…”
Section: Article In Pressmentioning
confidence: 99%
“…The observation that skeletal muscle of aged individuals shows increased relaxation times has been correlated with a potential age-related dysfunction of the sarcoplasmic reticulum (SR) Ca-ATPase [14]. Pending a detailed analytical characterization of possible age-related covalent modifications of this protein, it appears reasonable that reactive oxygen species could be responsible for such modifications since they are actively involved in the modulation of skeletal muscle function [15,16]. For example, superoxide dismutase-sensitive reactive oxygen species have been found to account for 85% of a 6-fold increase of cytochrome c reducing equivalents in actively contracting muscle as compared to resting muscle [16], suggesting a specific role for superoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Pending a detailed analytical characterization of possible age-related covalent modifications of this protein, it appears reasonable that reactive oxygen species could be responsible for such modifications since they are actively involved in the modulation of skeletal muscle function [15,16]. For example, superoxide dismutase-sensitive reactive oxygen species have been found to account for 85% of a 6-fold increase of cytochrome c reducing equivalents in actively contracting muscle as compared to resting muscle [16], suggesting a specific role for superoxide. Moreover, it has been demonstrated that constitutive nitric oxide synthase is highly expressed in skeletal muscle [17] and that nitric oxide (NO) may modulate skeletal muscle contraction [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation